The Campus Canopy, 1938-11-11 - The Campus Canopy, The Georgia State Woman's College (The Georgia State Woman's College, 1938)
The Campus Canopy, November 11, 1938. Vol. 7, No. 8. Craftwork Exhibited By Fine Arts Club -- What Goes On Here In GSWC Classrooms -- Lambdas Again Take All Honors -- Weary Delegates Tell Of Thrilling Experiences -- Blue Ribbon Horse Trainer Exhibits Gaits -- Sophomores Plan Dance -- Technical And Popular Books Added To Shelves -- IRC Presents Varied Program At Monday Forum -- Tyrone Powder In Suez A Definite Hit At GSWC
Georgia State Womans College Student Newspaper
Digitized from original print, Valdosta State University Archives and Special Collections, November 29, 2016.
Keywords: Valdosta State University -- Periodicals